Efektivitas Penyelenggaraan Pelatihan Desain Grafis di Balai Pelatihan Vokasi dan Produktivitas Padang - Saniyyah Aulia Azzahra; Artha Dini Akmal (YASIN, 2026)
The implementation of graphic design training at BPVP Padang still faces several problems, including a manual attendance system, institutional responsibility that has not yet extended to job placement, obstructed alumni monitoring, low labor absorption of alumni, and the suboptimal achievement of trainees’ employment targets. This study aimed to analyze the effectiveness of graphic design training implementation at BPVP Padang and to identify the supporting and inhibiting factors that influence it. This study used a descriptive qualitative approach. Data were collected through interviews and documentation by using primary and secondary data sources, and were then analyzed through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results showed that the implementation of graphic design training at BPVP Padang had been fairly effective in terms of goal achievement, integration, and adaptation. In the aspect of goal achievement, the training had contributed to improving participants’ competence, although alumni data collection remained an obstacle in evaluating the program’s contribution to reducing unemployment. In the aspect of integration, the institution’s internal and external cooperation had been fairly effective, but the quality of communication between instructors and participants still needed to be improved. In the aspect of adaptation, the institution had been able to adjust to training needs through the availability of adequate facilities, infrastructure, and instructors, although the attendance system was still carried out manually. The supporting factors for training effectiveness included a curriculum aligned with SKKNI as well as high participant participation and focus, while the inhibiting factors included manual attendance, obstructed alumni monitoring, miscommunication, and budget limitations. The conclusion of this study emphasizes that the effectiveness of graphic design training at BPVP Padang needs to be strengthened through the digitalization of the attendance system, improvement of training communication, optimization of alumni monitoring, and strengthening of budget support so that the training program can contribute more effectively to improving participants’ competence and employability.